The practice of participatory action research: Complicity, power and prestige in dialogue with the 'racialised mad'. (24th August 2022) - Haarmans, Maria; Nazroo, James; Kapadia, Dharmi; Maxwell, Charlotte; Osahan, Sonja; Edant, Jennifer; Grant‐Rowles, Jason; Motala, Zahra; Rhodes, James
Abstract: Mental health service users in the UK have become increasingly involved in research over the last 2 decades partly as a consequence of research governance. Ethnic minority service users, however, point to power imbalances stemming from marginalisation and discrimination creating barriers to knowledge co‐production (Kalathil, J. (2013). Hard to reach? Racialised groups and mental health service user involvement.). Heavily influenced by Freire's liberatory education, participatory action research (PAR) repoliticises participation where those most affected by injustice are central in both producing knowledge about injustice and implementing solutions. Ethnic minority people with lived experience of 'severe mental illness' ('the racialised mad') were appointed as coresearchers to work with academic researchers on a qualitative study exploring ethnic inequalities in 'severe mental illness'. Drawing on Foucault's notion of power as relational, we focus on three key aspects of productive power: (1) relational engagement and reciprocity, (2) positioning coresearchers as authentic researchers and (3) adopting an ethic of care, to explore complicity and resistance in reproducing hierarchies of knowledge and power when attempting to create and sustain a PAR process for collective analysis, action and solidarity. We utilise retrospective and recorded reflections over the course of the project. Finally, we discuss the ethical and methodological implications for contemporary sociological research into health and illness.